Hubungan Kekuatan Otot Lengan, Koordinasi Mata Tangan Terhadap Kemampuan Passing Bawah Siswi Ekstrakurikuler MTS Negeri 1 Sukabumi - Muhamad Abdurrahman; Firman Septiadi; Rizky Adi Wijaya (Universitas Negeri Medan, 2019)
This study aims to determine the relationship between arm muscle strength and hand eye coordination on the passing ability of the extracurricular student volleyball game at MTs Negeri 1 Sukabumi. The method used in this study is a quantitative approach to the correlational method. The research sample was 18 volleyball extracurricular students at MTs Negeri 1 Sukabumi, with a sampling technique using saturated samples. The data obtained is then processed. The result is a significant relationship between arm muscle strength and hand eye coordination to the passing ability of the extracurricular student volleyball game at MTs Negeri 1 Sukabumi. The results of calculations using the multiple correlation technique obtained Fcount greater than Ftable, namely Fcount (149,153)> Ftable (4.49) with a significant level of 0.05 then H0 is rejected meaning that there is a significant relationship between arm muscle strength and hand eye coordination passing ability under the extracurricular student volleyball game MTs Negeri 1 Sukabumi. The conclusion of the study is that there is a significant relationship between arm muscle strength and hand eye coordination on the passing skills of volleyball in extracurricular MTs Negeri 1 Sukabumi